Anxiety and Love in the Album “Dunia Batas” by Payung Teduh: A Hermeneutical Review - Firdaus, Afrizal Cahya; Ahmadi, Annas (Wacana : Jurnal Bahasa, Seni, dan Pengajaran, 2025)
This study explores how anxiety and love intertwine in the lyrics of Payung Teduh’s album Dunia Batas through Schleiermacher’s hermeneutic framework, which fuses grammatical and psychological interpretation. Employing a qualitative descriptive design, six key tracks—“Berdua Saja,” “Menuju Senja,” “Untuk Perempuan yang Sedang di Pelukan,” “Angin Pujaan Hujan,” “Resah,” and “Di Ujung Malam”—were analyzed for their symbolic language, metaphorical imagery, and narrative structure. Grammatical analysis uncovers recurring motifs—the night as a realm of intimacy, roses as emblems of love’s paradoxical beauty and pain, and the branching wind as a metaphor for emotional uncertainty. Psychological analysis delves into the songwriter’s emotional context, revealing an inner tension between the hope for connection and the fear of rejection. Findings demonstrate that Dunia Batas orchestrates a continuous poetic dialogue between longing and unrest, conveyed through its evocative lyrics, gentle melodies, and rich harmonies. By highlighting song lyrics as both artistic expressions and reflections of contemporary social–psychological dynamics, this research advances the study of music hermeneutics in Indonesia.